Liver X Receptor Alpha Activation Inhibits Autophagy and Lipophagy in Hepatocytes by Dysregulating Autophagy‐Related 4B Cysteine Peptidase and Rab‐8B, Reducing Mitochondrial Fuel Oxidation. Issue 4 (16th March 2021) - Kim, Yun Seok; Nam, Hyeon Joo; Han, Chang Yeob; Joo, Min Sung; Jang, Kiseok; Jun, Dae Won; Kim, Sang Geon
Abstract : Background and Aims: Fat accumulation results from increased fat absorption and/or defective fat metabolism. Currently, the lipid‐sensing nuclear receptor that controls fat utilization in hepatocytes is elusive. Liver X receptor alpha (LXRα) promotes accumulation of lipids through the induction of several lipogenic genes. However, its effect on lipid degradation is open for study. Here, we investigated the inhibitory role of LXRα in autophagy/lipophagy in hepatocytes and the underlying basis. Approach and Results: In LXRα knockout mice fed a high‐fat diet, or cell models, LXRα activation suppressed the function of mitochondria by inhibiting autophagy/lipophagy and induced hepatic steatosis. Gene sets associated with "autophagy" were enriched in hepatic transcriptome data. Autophagy flux was markedly augmented in the LXRα knockout mouse liver and primary hepatocytes. Mechanistically, LXRα suppressed autophagy‐related 4B cysteine peptidase (ATG4B) and Rab‐8B, responsible for autophagosome and ‐lysosome formation, by inducing let‐7a and microRNA (miR)‐34a. Chromatin immunoprecipitation assay enabled us to find LXRα as a transcription factor of let‐7a and miR‐34a. Moreover, 3' untranslated region luciferase assay substantiated the direct inhibitory effects of let‐7a and miR‐34a on ATG4B and Rab‐8B. Consistently, either LXRα activation or the let‐7a/miR‐34a transfection lowered mitochondrial oxygen consumption rate and mitochondrial transmembrane potential and increased fat levels. In obese animals or nonalcoholic fatty liver disease (NAFLD) patients, let‐7a and miR‐34a levels were elevated with simultaneous decreases in ATG4B and Rab‐8B levels. Conclusions: LXRα inhibits autophagy in hepatocytes through down‐regulating ATG4B and Rab‐8B by transcriptionally activating microRNA let‐7a‐2 and microRNA 34a genes and suppresses mitochondrial biogenesis and fuel consumption. This highlights a function of LXRα that culminates in the progression of liver steatosis and steatohepatitis, and the identified targets may be applied for a therapeutic strategy in the treatment of NAFLD.